Динаміка взаємодії плівки рідини та газового потоку у вертикальних каналах тепломасообмінного обладнання ГТУ компресорних станцій - Tuz V.E.; Bilodid V.D.; Lebed N.L. (General Energy Institute of the National Academy of Sciences of Ukraine, 2009)
The results of experimental research of minimum closeness of irrigation in channels with net coverage of walls heat and mass transfer equipment of preparation technological and fuel gas of the systems of gas industry enterprises are resulted.